The "oral" history of COVID‐19: Primary infection, salivary transmission, and post‐acute implications. Issue 10 (7th September 2021) - Marchesan, Julie Teresa; Warner, Blake M.; Byrd, Kevin Matthew
Abstract: Severe acute respiratorysyndrome coronavirus 2 (SARS‐CoV‐2), the causative agent of COVID‐19, has led to more than 3.25 million recorded deaths worldwide as of May 2021. COVID‐19 is known to be clinically heterogeneous, and whether the reported oral signs and symptoms in COVID‐19 are related to the direct infection of oral tissues has remained unknown. Here, we review and summarize the evidence for the primary infection of the glands, oral mucosae, and saliva by SARS‐CoV‐2. Not only were the entry factors for SARS‐CoV‐2 found in all oral tissues, but these were also sites of SARS‐CoV‐2 infection and replication. Furthermore, saliva from asymptomatic individuals contained free virus and SARS‐CoV‐2‐infected oral epithelial cells, both of which were found to transmit the virus. Collectively, these studies support an active role of the oral cavity in the spread and transmission of SARS‐CoV‐2 infection. In addition to maintaining the appropriate use of personal protective equipment and regimens to limit microbial spread via aerosol or droplet generation, the dental community will also be involved in co‐managing COVID‐19 "long haulers"—now termed Post‐Acute COVID‐19 Syndrome. Consequently, we propose that, as SARS‐CoV‐2 continues to spread and as new clinical challenges related to COVID‐19 are documented, oral symptoms should be included in diagnostic and prognostic classifications as well as plans for multidisciplinary care.